Housing demand and tenure choice in Brazilian urban areas - Maria da Piedade Morais; Bruno de Oliveira Cruz (Institute for Applied Economic Research (ipea), 2017)
This paper analyzes the main determinants of tenure choice in Brazil in formal and informal housing markets. Logit and Multinomial Logit models with several specifications are used to test the household's tenure choice behavior taking demographic, social, economic and locational factors as dependent variables. The main source of information is the 2005 National Household Survey (Pnad) microdata. The probability of ownership is higher among non-afrodescendents, man-headed households and public servants. The poor, the young, recent migrants and single women with young children have higher probabilities of renting or becoming owners in informal settlements. Wealth and life cycle variables such as age, household size and marital status are good predictors for formal ownership. Education enhances the probability of being in the formal housing markets, either as a renter or an owner.
Keywords: R15; R21; R31; R38; 330; housing demand; tenure choice; housing policy; Brazil